PENGARUH METODE DRILL TERHADAP HASIL BELAJAR DAN MINAT BELAJAR MATEMATIKA SISWA SD NEGERI 2 CENGAL KABUPATEN OKI - Khoirun Nisa, Tia Heni; Kesumawati, Nila; Dedy, Adrianus (Jurnal Pendidikan Dasar, 2023)
The influence of appropriate learning methods will affect student learning outcomes and attitudes, especially in learning mathematics. This study aims to determine the effect of the drill method on learning outcomes and students' interest in learning mathematics at SD Negeri 2 Cengal. The population is 492 students, with a sample of 60 students from classes III—a and III.B. The research method used is the Quasi-Experimental Design Method with the Posttest-Only Control Group Design type. The data collection techniques used were only tests and questionnaires. While the process used to analyse the data is MANOVA (Multiple Analysis Of Variances). This study’s results indicate a significant effect of the drill method on learning outcomes and students' interest in learning mathematics simultaneously. In addition, there is a significant correlation between learning outcomes and learning interest so that learning becomes active. Using the right method is also the reason for active learning, which can increase learning outcomes and interest in education, one of which is the drill method which emphasises training.